Multiscale design of nanoengineered matrices for lead-free piezocomposites: Improved performance via controlling auxeticity and anisotropy. (1st January 2021) - Krishnaswamy, Jagdish A.; Buroni, Federico C.; Melnik, Roderick; Rodriguez-Tembleque, Luis; Saez, Andres
Abstract: Multiscale material design has made it possible to control the properties of a material through introducing structures at multiple length scales. This structuring brings about unusual material behaviour that is not seen in a continuum material. Here we introduce a multiscale design for the matrix components of a lead-free piezocomposite. This combines a microscale stiff polymeric structure embedded within a softer matrix to form a composite matrix. By controlling the microscale features of the embedded structure, we tune the mechanical behaviour of the matrix by rendering it either nonauxetic (hexagonal structure) or auxetic (inverted hexagonal structure). Further, the mechanical and electrical properties of the matrix are controlled at the nanoscale by addition of carbon nanotubes within the embedded polymeric structure. By engineering the matrix at the nano and the microscale, we firstly demonstrate that the auxetic matrix can result in three orders of magnitude higher piezoelectric response by amplifying the strains within the piezoelectric inclusions. We further demonstrate that by using the matrix with the nonauxetic embedded structure, it is possible to design piezoelectric composites with pronounced anisotropy in their longitudinal and transverse responses. This is an important requirement for designing materials with directional sensing ability. Our findings show that the multiscale material design proposed here has important implications for both energy harvesting and directional sensing. Further, the approach taken here yields considerable performance improvements while using limited quantities of nanomaterial. The multiscale matrix design is scalable and amenable to fabrication through emerging methods such as additive manufacturing.